1978
DOI: 10.1107/s0567740878007554
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic studies of interactions between nucleotides and metal ions. III. Two independent structural investigations of the polymeric complex of copper(II) with guanosine 5'-phosphate

Abstract: The results of the two independent X-ray analyses of the complex formed between cupric ions and the nucleotide guanosine 5'-monophosphate are presented and compared. The crystals are polymeric, with a spiralling sequence, (-Cu-phosphate-sugar-base-)oo, the turns of which are cross-linked by additional bonds between copper and phosphate O atoms and by hydrogen bonding between coordinated water molecules and phosphate O atoms. The purine bases project outwards from the spiral and intercalate between bases of nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Similar chelate formation through the guanine N-7 and the phosphate groups on the same DNA strand was previously proposed for Cu-DNA complexe~.~ It is important to note that copper ion binding to the guanine N-7 and the PO:-group of the GMP anion is known through x-ray diffraction measurements. 21 The cytosine bands at 1529,1492,1424, and 1374 cm-' exhibited no major spectral changes on copper ion interaction and thus, no Cu-cytosine binding can be expected (Table I ) . It has been shown that -19 kcal/mol energy barrier should be provided before the most reactive cytosine sites become accessible for metal ion coordination, and this value is far more than -7.5 kcal/mol for DNA denaturation energy.…”
Section: Results a N D Discussionmentioning
confidence: 94%
“…Similar chelate formation through the guanine N-7 and the phosphate groups on the same DNA strand was previously proposed for Cu-DNA complexe~.~ It is important to note that copper ion binding to the guanine N-7 and the PO:-group of the GMP anion is known through x-ray diffraction measurements. 21 The cytosine bands at 1529,1492,1424, and 1374 cm-' exhibited no major spectral changes on copper ion interaction and thus, no Cu-cytosine binding can be expected (Table I ) . It has been shown that -19 kcal/mol energy barrier should be provided before the most reactive cytosine sites become accessible for metal ion coordination, and this value is far more than -7.5 kcal/mol for DNA denaturation energy.…”
Section: Results a N D Discussionmentioning
confidence: 94%
“…As a result of the loss of the bridging water, the side chain of Glu-43 moves 0.3 Á closer to the metal. The resulting 4.4 Á metal-to-oxygen distance is, however, still too large for direct coordination of the metal by Glu-43; small molecule crystallographic studies [e.g., see Poojary and Manohar (1986) and Clark and Orbell (1978)] have shown that the typical Co2+-oxygen coordination bond length is approximately 2.0-2.2 Á. In the Co2 metal ion binding pocket there are no potential liganding partners within that distance that might replace the missing equatorial water.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the soft Pt(II) ion binds preferably to the N7 of guanine and adenine residues on DNA, while hard metal ions such as Mg(II) show a preference for phosphate groups [37,38,39]. For borderline metal ions such as Cu(II) and Mo(IV), simultaneous coordination to both N7 and phosphate group of GMP has been revealed by X-ray crystallographic studies [10,40]. Ti(IV) is essentially a hard metal ion in the``HSAB'' classi®-cation.…”
Section: Cleavage Of Atp Phosphoester Bonds By Cp 2 Ticlmentioning
confidence: 96%